DIGITAL DISCIPLESHIP DAN MENTAL HEALTH: IMPLIKASI TEOLOGIS BAGI PEMBENTUKAN IMAN REMAJA KRISTEN DI DUNIA VIRTUAL - Corina Tangdiombo; Inriyani; Putri Wahyuni Dewanto; Deventi Krislia Panggalo; Presdioyono (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study aims to analyze the relationship between digital discipleship and mental health in the faith formation of Christian teenagers in virtual worlds. Employing a qualitative library‑research design, it integrates practical theology, adolescent psychology, and digital media studies within the framework of discipleship theology and shalom. The findings indicate that digital discipleship practices such as hybrid worship, online small groups, and mentoring through social media provide wide access to biblical teaching and communal support, yet simultaneously emerge amid high levels of anxiety, loneliness, and performative spirituality. The virtual world is therefore understood as an ambivalent locus theologicus: a space of faith formation and a potential source of mental‑health risks. The article proposes conceptual categories such as healing digital liturgies, faith communities as counter‑communities to algorithmic culture, and digital Sabbath as a Christian discipleship discipline, and outlines practical implications for youth discipleship curricula and pastoral care.